(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
In the following article the modern methods of perfection of the cognitive competencies of the students in teaching the lesson of drawing are analyzed based on the available data. The article provides information about the Department of drawing and drafting Sciences.